1997
DOI: 10.1023/a:1007465907571
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract. We present an off-line variant of the mistake-bound model of learning. This is an intermediate model between the on-line learning model (Littlestone, 1988) and the self-directed learning model (Goldman, Rivest & Schapire, 1993, Goldman & Sloan, 1994. Just like in the other two models, a learner in the off-line model has to learn an unknown concept from a sequence of elements of the instance space on which it makes "guess and test" trials. In all models, the aim of the learner is to make as few mistak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Hal ini ditunjukkan seperti terjadinya diskusi akademik secara vertical (siswa dengan guru) dan horizontal (siswa dengan siswa) melalui tugas kelompok yang diberikan (Villela, 2013). Serta dalam pembelajaran offline tidak memiliki apa yang ada dalam pembelajaran online yaitu ketidakpastian akan fungsi yang ditargetkan tidak konsisten (siswa) dalam mengikuti pembelajaran dan tantangan masa depan bagi pembelajar online menghadapai depersonalisasi dalam relasi sosial (Ben-David et al, 1997). Serta 48,3 % siswa mengalami kelalaian selama kelas online dan 71,6% merasakan tidak puas dengan materi yang diberikan saat proses pembelajaran online.…”
Section: Pendahuluanunclassified
“…Hal ini ditunjukkan seperti terjadinya diskusi akademik secara vertical (siswa dengan guru) dan horizontal (siswa dengan siswa) melalui tugas kelompok yang diberikan (Villela, 2013). Serta dalam pembelajaran offline tidak memiliki apa yang ada dalam pembelajaran online yaitu ketidakpastian akan fungsi yang ditargetkan tidak konsisten (siswa) dalam mengikuti pembelajaran dan tantangan masa depan bagi pembelajar online menghadapai depersonalisasi dalam relasi sosial (Ben-David et al, 1997). Serta 48,3 % siswa mengalami kelalaian selama kelas online dan 71,6% merasakan tidak puas dengan materi yang diberikan saat proses pembelajaran online.…”
Section: Pendahuluanunclassified
“…Several studies have revealed online and offline learning systems (Almaiah et al, 2020;Ben-David et al, 1997;Firmansyah et al, 2021;Hari et al, 2020;Koeswanti, 2021;Najib & Mursidi, 2021;Singh et al, 2021;Wua et al, 2022), even another paper proposed the integration of both (Lalima & Lata Dangwal, 2017), and some researchers compared both (Gupta, 2021;Pei & Wu, 2019;Singh et al, 2021;Valentino et al, 2021). The primary objective of both online and offline learning is to provide quality education, hence they are similar to two opposite sides of the same coin (Gupta, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although boosting is initially introduced in the batch setting (Freund and E.Schapire (1997)), where algorithms boost themselves over a fixed set of training data, it is later extended to the online setting (Oza and Russell (2001)). In the online setting, however, we neither need nor have access to a fixed set of training data, since the data samples arrive one by one as a stream (Ben-David et al (1997); Fern and Givan (2003); Lu et al (2016)). Each newly arriving data sample is processed and then discarded without any storing.…”
Section: Introductionmentioning
confidence: 99%